Ibn Attiya's and Al-baidawee's Curriculum in the Quranic Readings "Comparative Study" (Abhat Journal, 2024)
This research deals with Quranic readings at Imam Ibn Attiya and the Al-baidaw Imam through their books. The research came in an introduction, researchers and a conclusion that addressed the importance of the subject, the reasons for its choice, its objectives, the problem of research and its divisions. The first study contained two requirements: The first requirement is a brief translation of Ibn Atiyah and the Al-Badawi. The second requirement is to make readings known, their relevance and the wisdom of their multiplication. The second examined two requests: The first requirement is Ibn Atiyah's approach to readings through his brief editor book. The second requirement is the Al-Badawi  approach to readings through his book Inawr Altanzial.      The conclusion mentioned the main findings and recommendations, the most important of which were:1- Quranic readings enrich interpretation, multiple meanings and connotations.2-The great usefulness of both interpretations in different sciences, especially with regard to readings.3-Imam Ibn Attiyah distinguished in mentioning the readings are true and anomalous and attributes each reading to its owner, directs them, and the Al-Badawi  Imam is limited to the seven readings and may sometimes mention the reading of Jacob Hadrami.
Keywords: readings; curriculum, ibn atiyah; Al-baidawee; Comparative study